Актуальні науково-методичні проблеми фізики та математики у закладах вищої освіти - Національний університет харчових технологій (My University, 2020)
Видання містить матеріали Всеукраїнської науково-методичної інтернет-конференції «Актуальні науково-методичні проблеми фізики та математики у закладах вищої освіти». На конференції розглянуті сучасні математичні методи в інженерних задачах, сучасні проблеми фізики та нові методи їх досліджень, а також методичні проблеми викладання фізики та математичних дисциплін у вищій школі. У матеріалах висвітлено шляхи і методи інтенсифікації навчального процесу й вплив новітніх наукових розробок на формування майбутніх фахівців. Proceedings of the All-Ukrainian Scientific and Methodological Internet Conference "Actual Scientific and Methodological Problems of Physics and Mathematics in Higher Education Institutions", 26 to 27 May, 2020 – K.: NUFT, 2020 – 187 p The conference is dedicated to the 90th anniversary of the Department of Physics and the Department of Higher Mathematics. prof. Mozhar V.I. The publication contains materials of the All-Ukrainian scientific and methodological Internet conference "Actual Scientific and Methodological Problems of Physics and Mathematics in Higher Education Institutions." The conference discusses modern mathematical methods in engineering problems, modern .problems of physics and new methods for their study, as well as methodological problems of teaching physics and mathematical disciplines at the university. The materials highlight the ways and methods of intensifying the educational process and the impact of the latest scientific developments on the formation of future specialists.
Keywords: викладання дисципліни; математика; фізика; новітні наукові розробки; teaching a discipline; physics; mathematics; latest scientific developments